Students’ Perceptions of Lecturers’ TPACK Competence in Digital Project-Based Learning - Mustari S. Lamada; Dwi Rezky Anandari Sulaiman; Shabrina Syntha Dewi; Aulyah Zakilah Ifani (Jurusan Teknik Informatika dan Komputer, 2025)
The acceleration of digital transformation in higher education requires lecturers to demonstrate strong Technological Pedagogical and Content Knowledge (TPACK), especially when implementing Project-Based Learning (PjBL). However, limited empirical evidence exists on how students perceive lecturers’ digital-integrative competence within project-based contexts in Southeast Asia. This study aims to examine students’ perceptions of lecturers’ TPACK competence in integrating digital technology within PjBL settings. Using a quantitative survey design, data were collected from 42 engineering students at Universitas Negeri Makassar. Descriptive statistics and Spearman correlation analyses were conducted across seven TPACK dimensions. Results revealed that students rated lecturers’ TPACK competence from moderate to high, with the strongest correlation between Pedagogical Content Knowledge (PCK) and overall TPACK (rₛ = 0.809, p < 0.001). This finding underscores the importance of combining pedagogical and content expertise to enhance digital instruction. The study implies that institutional training focused on pedagogical–technological integration may further strengthen lecturers’ digital teaching performance.